Stereoselective allylation of acyclic and chiral α-amino-β-Hydroxy aldehydes part 2: Application to the formal synthesis of the polyhydroxylated γ-amino acid (+)-Detoxinine. Issue 28 (12th July 2018) - Myeong, In-Soo; Lee, Sang-Hyun; Ham, Won-Hun
Abstract: Stereoselective allylations of acyclic, chiral α-amino-β-hydroxy aldehydes mediated by BF3 ·OEt2 and its application to the formal synthesis of the polyhydroxylated γ-amino acid (+)-detoxinine are described. The reactions of syn -α-NHCbz-β-OTBS substrates mediated by BF3 ·OEt2 afforded syn -selective products. The same reaction conditions gave anti -selective products from syn -α-NCbzBn-β-OTBS substrates. A hydrogen-bonded transition state and Felkin-Anh model have been suggested to account for the stereochemical outcomes of the two reactions, respectively. One of the allylation products was used for the formal synthesis of the polyhydroxylated γ-amino acid (+)-detoxinine. Graphical abstract: Image 1